Linkages between oral commensal bacteria and atherosclerotic plaques in coronary artery disease patients - Jyoti Chhibber-Goel (Nature Portfolio, 2016)
Heart disease: Links to oral bacteria A review of bacterial populations in the mouth and in diseased arteries will help research into the role of bacteria in heart disease. Amit Sharma and colleagues at the International Centre for Genetic Engineering and Biotechnology, with co-workers at the All India Institute of Medical Sciences, both in New Delhi, India, analyzed 63 studies covering 1791 patients spread over a decade. They summarize evidence of 23 types of oral bacteria that are also found in atherosclerotic plaques in artery walls. The review also cataloged the proteins secreted by the bacteria and discussed possible involvement of these proteins in the migration of bacteria through the bloodstream. Full genetic details are available for 19 of the 23 bacterial species, which should greatly assist further investigations into the significance of bacteria in the onset of heart disease.